2021
DOI: 10.3390/rs13163298
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic of Vegetation Growth with Regular Climate and Climatic Fluctuations in a Subtropical Mountainous Island, Taiwan

Abstract: Vegetation phenology is an integrative indicator of environmental change, and remotely–sensed data provide a powerful way to monitor land surface vegetation responses to climatic fluctuations across various spatiotemporal scales. In this study, we synthesize the local climate, mainly temperature and precipitation, and large-scale atmospheric anomalies, El Niño-Southern Oscillation (ENSO)-connected dynamics, on a vegetative surface in a subtropical mountainous island, the northwest Pacific of Taiwan. We used tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 123 publications
(160 reference statements)
0
6
0
Order By: Relevance
“…The cross‐scale monitoring of temporal dynamics in vegetation growth and litterfall is crucial for understanding the impact of climatic fluctuations on terrestrial ecosystems (Lin et al., 2017; Wang et al., 2016; Wang & Chang, 2021). In this study, we found that the time‐lag effect plays a crucial role in coordinating the temporal dynamics of litterfall and the EVI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cross‐scale monitoring of temporal dynamics in vegetation growth and litterfall is crucial for understanding the impact of climatic fluctuations on terrestrial ecosystems (Lin et al., 2017; Wang et al., 2016; Wang & Chang, 2021). In this study, we found that the time‐lag effect plays a crucial role in coordinating the temporal dynamics of litterfall and the EVI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is imperative not only to investigate the impacts of drought or typhoons on MCFs but also to discern how MCFs respond to these disruptions. Understanding how disturbances specifically alter vegetation phenology remains a relatively unexplored area, even though changes in phenology provide valuable insights into the adaptive strategies of vegetation in response to climatic fluctuations (Wang & Chang, 2021). Moreover, delving into the responses of carbon dynamics within the ecosystems to these perturbations is pivotal for assessing how MCFs manage their carbon equilibrium in the face of such disruptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer this question, specific goals and objectives for various types of research must be implemented. At the same time, a digital forest model based on remote sensing data and obtained inventory data will allow us to determine the resources that need to be carefully managed, realizing the vital ecosystem value of forests [52][53][54][55]. Despite the initial difficulties in building a forest model, the peculiarity of organizing and preserving digital data allows An essential task in developing the model was creating an environment for interaction with the model and its functional features; to implement this task, intelligent geoinformation system technologies were used [42][43][44].…”
Section: Data Integrationmentioning
confidence: 99%
“…The temperature has long been the dominant control factor in global vegetation trends, especially in the higher latitude and altitude areas [6,7,12]. A recent study conducted by Wang and Chang (2021) [80] performed a detailed assessment of the relationships between vegetation, climatic factors, and non-climatic factors at multiple timescales across various land cover types in Taiwan; based on their findings, temperature and precipitation play important roles in vegetation growth; however, the effects vary across seasons. The conclusions of Wang and Chang (2021) [80] correspond to the statement presented by Piao et al (2014) [81], who recognized that the relationship between vegetation and climate factors might change over time due to the changes in climate and other environmental factors [81].…”
Section: Occurrence Of Breakpointsmentioning
confidence: 99%